Perbandingan Sistem Pendidikan di Tiga Negara; Mesir, Iran dan Turki - Ihsan, M Nurul; M Nurul Ikhsan Saleh (Faculty of Tarbiyah and Education, Universitas Islam Negeri (UIN) Sunan Kalijaga Yogyakarta, 2015)
AbstractThis article discusses a comparative analysis of education in three countries where the population is predominantly of a Muslim background; Egypt, Iran, and Turkey, and explains the system of education in primary schools, secondary schools, and colleges. Additionally, this article clarifies the latest education policy, curriculum, subjects, and assessment systems in schools and universities. The three countries have some similarities; each country is implementing the policy of compulsory education with it split into three levels. The other similarity being that is the students have a high interest in further study in foreign universities with some destination countries being: the United States of America, the United Kingdom, Germany, Saudi Arabia, Canada, Ukraine, Malaysia, France, and Austria. Due to unfavorable politics in both countries of Egypt and Turkey, as well as Iran, education has been affected by a foreign policy that is often contradictory.